Gamma-glutamyltransferase, alanine transaminase and aspartate transaminase levels and the diagnosis of gestational diabetes mellitus - Tan, P.C.; Aziz, A.Z.; Ismail, Ikram Shah; Omar, S.Z. (Elsevier, 2012)
Objectives: To evaluate gamma-glutamyltransferase (GGT), alanine transaminases (ALT) and aspartate transaminases (AST) levels and prevalent gestational diabetes mellitus (GDM). Design and methods: Random plasma glucose, GGT, ALT and AST and the 50-g glucose challenge test were done on antenatal women followed by diagnostic 3-point 75-g oral glucose tolerance test within two weeks. GDM was diagnosed by ADA (2011) criteria. Results: The GDM rate was 12.2 (319/2610). Mean GGT level was higher in GDM women, 18 12 vs. 16 11 IU/L; P=0.03. The risk for GDM was higher for women in the highest GGT quartile band compared to the lowest: RR 1.35 95CI 1.0-1.8; P=0.04. However, after adjustment for confounders, GGT was no longer associated with GDM. There was no correlation between ALT and AST levels and GDM. Conclusions: Liver transaminases do not predict GDM in contrast to type 2 diabetes. (C) 2012 The Canadian Society of Clinical Chemists. Published by Elsevier Inc. All rights reserved.